Robotics in Schools as a Way of Promoting Science and Engineering - Almeida, Aline Gabriela Loiola; Coimbra, William Alves e; Santos, Dércio Manique Sanches Dos; Pimentel, Luiz Felipe Lacerda; Araujo Junior, Lindolpho Oliveira de (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2025: Anais do XVII Simpósio Brasileiro de Robótica e XVI Workshop de Robótica na Educação, 2025)
Maker culture and educational robotics are approaches that foster experimentation, creativity, and logical reasoning. However, a decline in young people's interest in scientific and engineering careers has been observed in Brazil. To reverse this trend, the ROBESC (Robótica Escolar) project proposes an innovative approach by integrating maker culture into robotics education in public schools and vulnerable communities. The methodology comprises two-day workshops introducing robotics concepts, the assembly and programming of LEGO®MINDSTORMS®NXT robots for a sumo competition, all guided by engineering students. Results-based on pre- and post-workshop surveys administered in three schools-indicate that most participants, who initially had no prior knowledge of the subject, reported being moderately capable of applying robotics concepts. Through the project, students developed different robot architectures and programming strategies, enhancing logical reasoning, programming fundamentals, and teamwork. It is concluded that ROBESC proves to be an effective tool for disseminating science and engineering, stimulating student interest, and strengthening both hard and soft skills, thereby forging a vital link between higher education and basic education.